2019
DOI: 10.3390/en12234582
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of a 10 MW Prototype Kaplan Turbine during Start-Up Operation

Abstract: An increase in the start/stop cycles of hydraulic turbines due to the penetration of intermittent renewable energy sources is important. Hydraulic instabilities that occur in hydraulic turbines during start/stops may cause structural issues in the turbine components. High-stress fluctuations on the runner blades are expected during start-ups due to the unsteady pressure loading on the runner blades. This paper presents experiments performed on a 10 MW prototype Kaplan turbine at the Porjus Hydropower Center du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…A dominant frequency of is also observed in Figure 17 f, which is for deep part load operation (OP0). A dominant frequency in the same range was observed in a load increase from speed-no-load in a Kaplan and propeller turbine [ 20 , 23 ]. This frequency, which could be related to the vortical flow structures in the vaneless space, occurred at speed-no-load operation and moved below the runner by increasing the discharge.…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…A dominant frequency of is also observed in Figure 17 f, which is for deep part load operation (OP0). A dominant frequency in the same range was observed in a load increase from speed-no-load in a Kaplan and propeller turbine [ 20 , 23 ]. This frequency, which could be related to the vortical flow structures in the vaneless space, occurred at speed-no-load operation and moved below the runner by increasing the discharge.…”
Section: Resultsmentioning
confidence: 81%
“…This frequency, which could be related to the vortical flow structures in the vaneless space, occurred at speed-no-load operation and moved below the runner by increasing the discharge. It was previously found that the variation of the dominant frequency related to vortical flow structures ( ) was accompanied by the variation of the low frequency ( ) at the same time period but in the opposite direction [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations